2001
DOI: 10.1101/gr.205301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Interaction Networks Using Sequence-Based Searches for Conserved Protein-Protein Interactions or “Interologs”

Abstract: Protein interaction maps have provided insight into the relationships among the predicted proteins of model organisms for which a genome sequence is available. These maps have been useful in generating potential interaction networks, which have confirmed the existence of known complexes and pathways and have suggested the existence of new complexes and or crosstalk between previously unlinked pathways. However, the generation of such maps is costly and labor intensive. Here, we investigate the extent to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
349
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(365 citation statements)
references
References 24 publications
6
349
0
6
Order By: Relevance
“…An indicator of related functions is similar protein-protein interaction patterns. One such special case are the ''interlogs'' (i.e., pairs of interacting proteins that interact identically in two species) (19). It has already been demonstrated that the information about the interacting partners can be used to predict the fold (7,(20)(21)(22) or function (14,(23)(24)(25)(26)(27)) of a protein without considering its sequence.…”
Section: Detecting Remotely Related Proteins By Their Interactions Anmentioning
confidence: 99%
“…An indicator of related functions is similar protein-protein interaction patterns. One such special case are the ''interlogs'' (i.e., pairs of interacting proteins that interact identically in two species) (19). It has already been demonstrated that the information about the interacting partners can be used to predict the fold (7,(20)(21)(22) or function (14,(23)(24)(25)(26)(27)) of a protein without considering its sequence.…”
Section: Detecting Remotely Related Proteins By Their Interactions Anmentioning
confidence: 99%
“…Another well-known information is homology of PPIs across different species. Methods on this information simply find PPIs which are conserved across species, called interologs (Matthews et al, 2001). Here, any known PPIs regarded as query to find conserved interactions across species using an ortholog database.…”
Section: Computational Prediction Methods For Ppismentioning
confidence: 99%
“…In Figure 4, we illustrate how even with these caveats, a network constructed in yeast can form a tremendously useful scaffold for understanding the function of Caenorhabditis elegans genes. The networks may thus provide an objective view of gene function that can be transported between organisms, and perhaps iteratively improved with data from across organisms 47,53,54 . Thus, one might consider constructing a universal network, the union of individual organisms' networks, perhaps with linkages and vertices flagged by the organisms from which they derive (such as in the Genome Knowledgebase; http://www.genomeknowledge.org/), that would represent the cumulative body of knowledge of gene function, even across evolutionary divergence of the systems.…”
Section: The Universal Networkmentioning
confidence: 99%